Nexus thinking for sustainable irrigation - Taye, Meron Teferi (CGIAR System Organization, 2023)
On the 8th International Day of Women & Girls in Science, clean water and sanitation are front and center. Within the framework of the Sustainable Development Goals, the high-level sessions at the United Nations Headquarters in New York will advocate for women in science. Importantly, the agenda also recognizes the role of women in the communities targeted by development programs. On both fronts, observes IWMI Researcher Dr Meron Teferi Taye, “There’s more awareness than before. But on the ground, it’s not always the case that gender mainstreaming has taken place.”